The application of a natural chitosan/bone char composite in adsorbing textile dyes from water. Issue 9 (2nd September 2017) - Hossini, Hooshyar; Darvishi Cheshmeh Soltani, Reza; Safari, Mahdi; Maleki, Afshin; Rezaee, Reza; Ghanbari, Reza
ABSTRACT: Colored wastewaters are one of the common waste contaminants which are derived from various industries, threatening aquatic environments. Thus, it is necessary to treat them before discharge. Among various remediation technologies, adsorption is one of the popular treatment methods because of its simplicity and cost-efficiency. So, in the present study, the adsorption potential of a natural chitosan/bone char composite was investigated in adsorbing the Direct Brown 166 dye (DB-166) from aqueous solution. To investigate the adsorption potential of the chitosan/bone char composite, the effects of influencing parameters were studied. Accordingly, the optimum removal efficiency was determined at an initial pH of 3, a contact time of 60 min, an initial dye concentration of 20 mg/L, an adsorbent dosage of threatening 4 g, a mixing speed of 150 rpm, and a temperature of 55°C. Also, the maximum adsorption efficiency and capacity were obtained to be 99.8% and 21.18 mg/g, respectively. To evaluate the equilibrium and dynamics, isotherm and kinetic models were investigated. As a result, the Langmuir isotherm ( R 2  = 0.996) and pseudo-second-order kinetic model ( R 2  = 0.999) fitted the experimental data well. These results revealed that the chitosan/bone char composite can be used as an efficient adsorbent for the decolorization of aquatic solutions.